(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to demonstrate the role that resource consumption accounting technology can play in controlling costs and utilizing available resources, as well as helping to accurately determine the cost of the product to help reduce unjustified costs. The research community is represented by the Iraqi industrial companies, while the research sample is represented by the Al-Fida Public Company for the data of the year 2021. The research reached a set of conclusions, the most important of which was that the resource consumption accounting technique can help control costs and the exploitation of available resources by achieving self-monitoring of activities by going down in the cost analysis processes to the partial level, which is the level of resources and not on the basis of the macro level of the economic unit as a whole, and this helps in rationalizing the consumption of resources and controlling idle energy